Evaluating The Nexus of Renewable Energy's in Economic Growth Realities: Autoregressive Distributed Lag Approach - Kuncoro, Trian Gigih; Susanto, Deni Aditya (Gorontalo State University, 2024)
This article about energy in an economic context, energy fossil has become one of the causes of issues faced by humanity. These problems have cascading impacts, ranging from climate damage to individual health and global socio-economic conditions. This study aimed to elucidate the effects of renewable energy, fossil energy, labor force, foreign direct investment and carbon dioxide emissions on economic growth. The analytical tool employed was the ARDL bound test. Secondary data from annual series spanning from 1986 to 2020. The study found a two-way cointegration between labor force, foreign direct investment, and economic growth. Based on the methodology used, conclusions were drawn regarding short-run and long-run relationships. In the short run, both fossil and renewable energy had unidirectional relationships with economic growth. Carbon dioxide emissions had a negative impact on economic growth in the short-run and the long-run. Labor force and economic growth exhibited a two-way relationship in the long-run. Consequently, energy transition policies and the imposition of carbon emission taxes could have negative short-run implications for Indonesia's economic growth, while the reverse may be true in the long run. Economic growth may reach a peak and then decline and policymakers should maximize existing non-renewable energy sources. A policy requiring to control more fossil fuel energy sources and discover untapped reserves is worthy of continuation and even strengthening. The findings provide an understanding of the relationship between renewable energy and economic growth as a necessity for the energy transition. The study has limitations in assumptions when interpreting the findings.